Case Study of Legal Measures to Promote the Reforestation of Economic Woods in Thep Sathit District Chaiyaphum Province - Phiwkhaw, Wutthikrai; Wongbandit, Amnaj (Rajapark Journal, 2022)
The objectives of this research were: 1) to study Thai policies and laws that concern the promotion of the forestation of economic woods of Thailand; 2) to study the problems relating to the enforcement of laws relating to the promotion of the forestation of economic woods in the area of Thep Sathit District, Chaiyaphum Province; and 3) to suggest directions for promoting the forestation of economic woods in Thailand. This research work is a qualitative one whereby knowledge is attained through the study of documents such as articles, journals, and e-books from inside and outside the country. The findings from the research pointed out that the revision of Forest Act B.E. 2484 (A.D. 1941) (8th Revision) B.E. 2562 (A.D. 2019), in Article 7, has the substantial content that the logging or lumbering for using the land under or with the right of occupation or possession, which is still owned by the state, must be carried out in compliance with Forest Act B.E. 2484 (A.D. 1941). In the area of Thep Sathit Province, most of the land parcels in the area of Pa Nang Yang Klak National Park have problems concerning unclear borderlines that have led to difficulties in the enforcement of laws relating to lumbering in accordance with Forest Act B.E. 2484 (A.D. 1941). Consequently, the promotion of the forestation of economic woods has legal problems and obstacles, which have made the locals ignore the forestation of the economic and valuable timber in the area of Thep Sathit District, Chaiyaphum Province.